Predictors of Workplace Happiness among academicians in selected Public Higher Learning Institutions in Sarawak - Nur Fatihah, Abdullah Bandar; Zaiton, Hassan; SURENA, SABIL; Agatha Lamentan, Muda; Nur Fatihah, Mat Yusoff; LYDIA CI, LAW HUI (2025)
This study investigates the relationship between total rewards, work engagement, and work happiness among academicians in selected Public Higher Learning Institutions in Sarawak. Given the increasing pressures and expectations in academia, understanding the key factors contributing to work happiness is crucial for ensuring high performance, job satisfaction, and overall well-being. This study involved 158 respondents from selected Public Higher Learning Institutions in Sarawak. Using Pearson correlation and Multiple Linear Regression (MLR) analysis, the findings reveal that both total rewards and work engagement significantly predict work happiness, with total rewards exhibiting a stronger impact. The statistical results confirm that total rewards and work engagement together explain 72.6% of the variance in work happiness, demonstrating their critical role in fostering a positive and productive academic work environment. The study underscores the importance of developing comprehensive reward systems that encompass monetary, material, and non-monetary benefits to sustain and enhance work happiness among academicians. Additionally, fostering high levels of work engagement is essential to ensure that rewards translate effectively into long-term job satisfaction and commitment. Institutions that implement well-structured reward systems and engagement initiatives are more likely to retain motivated and dedicated academicians, leading to improved academic outcomes and institutional success. Moreover, this study provides insights for higher education policymakers and institutional leaders, highlighting the need to re-evaluate reward structures, engagement strategies, and support mechanisms to foster an environment conducive to both academic excellence and well-being. Addressing these factors can contribute to a more fulfilling and productive work environment, ultimately benefiting students, faculty, and the broader academic community. Future research should expand on these findings by exploring additional psychological and organizational factors that may further contribute to work happiness, such as leadership effectiveness, workplace culture, and career growth opportunities. The integration of qualitative insights alongside quantitative data could also provide a more comprehensive understanding of the underlying mechanisms influencing workplace happiness in academia.